Minimum Inhibitory Concentration Determination of Bambusa vulgaris Leaves Extract Against Skin and Digestive Diseases Bacteria - Kelly Zhiang; Rafika Sari; Pratiwi Apridamayanti (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2019)
Infections that are commonly happened in developing countries such as Indonesia are skin infection that caused by Staphylococcus aureus and Staphylococcus epidermidis, and digestive infection that caused by Bacillus subtilis and Bacillus cereus. The ethanol extract of Bambusa vulgaris leaves contained metabolite compounds that potential to have antibacterial activity. This study aimed to determine MIC (Minimum Inhibitory Concentration) value of ethanol extract of Bambusa vulgaris leaves against those four bacteria. The research was conducted by Kirby-Bauer disc diffusion method using ethanol extract of Bambusa vulgaris leaves with concentration variations of 80 mg/mL, 40 mg/mL, 20 mg/mL, 10 mg/mL, 5 mg/mL, 2.5 mg/mL, and 1.25 mg/mL. The results showed that ethanol extract of Bambusa vulgaris leaves can inhibit the growth of all four bacteria with MIC value against Staphylococcus aureus and Bacillus subtilis is 20 mg/mL, with inhibition zone diameter of 7,33 ± 0,416 mm and 6,32 ± 0,057 mm respectively. While the MIC value against Staphylococcus epidermidis and Bacillus cereus is 10 mg/mL, with inhibitory zone diameter obtained respectively 7,33 ± 0,416 mm and 6,07 ± 0,029 mm. The conclusion of this research was that ethanol extract of Bambusa vulgaris leaves had inhibition zone with MIC value 20 mg/mL against Staphylococcus aureus and Bacillus subtilis, and 10 mg/mL against Staphylococcus epidermidis and Bacillus cereus.Keywords: Ethanol extract of Bambusa vulgaris leaves, antibacterial, disc diffusion, MIC (Minimum Inhibitory Concentration)